Effect of verbal coach encouragement on rating perceived exertion and mood state during small sided games in professional soccer players - Selmi, O.; Bouassida, A. (MOJ Sports Medicine, 2017)
The purpose of this study was to compare the effects of coach encouragement during small-sided games (SSG) on mood state and rating of perceived exertion (RPE) in professionals` soccer players. Twenty soccer players (mean ± SD: age: 23 ± 0.9 years; height: 1.80 ± 0.09 m; weight: 74.05 ± 7.99 kg, %Fat: 11.05 ± 3.1 %)) took part in this study. Testing of players was conducted on separate days (each training session: 25-min: 4x4-min work with 3-min of passive recovery in-between) under two conditions with and without verbal encouragement during 4 vs. 4 SSG on a 24×35-m pitch size. Mood state was measured using the profile of mood state questionnaire (POMS). The players` heart rate (HR) was continuously measured, whereas ratings of perceived exertion (RPE) were collected after each bouts of SSG. RPE during SSGE and percent of HRmax (%HRmax) were higher in comparison than SSGNE (p<0.01). The SSGNE compared with SSGE resulted in: an increased total mood disturbance (p<0.01), tension (p<0.05) and a decreased vigor (p<0.01). SSGNE produced a mood disturbance while SSG ensured mood balance and high intensity. Our findings highlight the efficiency of verbal coach encouragement in games intensity and the psychological state.